Predatory protists play predominant roles in suppressing soil-borne fungal pathogens under organic fertilization regimes - Ren, Peixin; Sun, Anqi; Jiao, Xiaoyan; Shen, Ju-Pei; Yu, Dan-Ting; Li, Fangfang; Wu, Bingxue; He, Ji-Zheng; Hu, Hang-Wei (The Science of the total environment, 2023)
Soil-borne fungal pathogens pose a major threat to global agricultural production and food security. Pathogen-suppressive bacteria and plant beneficial protists are important components of soil microbiomes and essential to plant health and performance, but it remains largely unknown regarding how agricultural management practices influence the relative importance of protists and bacteria in plant disease suppression. Here, we characterized soil microbiomes (including fungi, protists, and bacteria) in bulk and sorghum rhizosphere soils with various long-term inorganic and organic fertilization regimes, and linked the changes in fungal plant pathogens with the protistan and bacterial communities. We found that the relative abundances of fungal pathogens were significantly decreased by organic fertilization regimes, and there was a significant difference in the community composition of fungal pathogens between inorganic and organic fertilization regimes. Organic fertilization significantly enhanced predatory protists but reduced the proportions of protistan phototrophs. Co-occurrence network analysis revealed more intensive connections between fungal plant pathogens with protists, especially predatory protists, than with bacterial taxa, which was further supported by stronger associations between the community structure of fungal pathogens and predatory protists. We identified more protist consumer taxa than bacterial taxa as predictors of fungal plant pathogens, and structural equation modelling revealed a more important impact of protist consumers than bacteria on fungal pathogens. Altogether, we provide new evidence that the disease inhibitory effects of long-term organic fertilization regimes could be best explained by the potential predation pressure of protists. Our findings advance the mechanistic understanding of the role of predator-prey interactions in controlling fungal diseases, and have implications for novel biocontrol strategies to mitigate the consequences of fungal infections for plant performance. [Display omitted] •Long-term organic fertilization regimes significantly reduced the relative abundances of fungal pathogens.•Organic fertilization significantly increased the proportions of predatory protists.•Predatory protists were the best predictors of the patterns of fungal plant pathogens.•The disease suppression of organic fertilization was best explained by the predation pressure of protists.•This study advanced our understanding of the crucial roles of trophic regulations in regulating fungal plant pathogens.